Pilot Study of Combined Tranexamic Acid Therapy in Breast Reduction – Intravenous and Local Infiltration - Margarida Silva; Pedro Machado; António Sousa Barros; António Costa-Ferreira (Aesthetic Plastic Surgery, 2026)
Abstract Background Tranexamic acid (TXA) reduces perioperative blood loss in several surgical fields; however, its role in breast reduction surgery remains unclear. This study aimed to evaluate the effect of combined TXA therapy (intravenous and local infiltration) on postoperative outcomes of patients who underwent modified Liacyr Ribeiro breast reduction. Methods We conducted a controlled, non-randomized pilot study of patients who underwent bilateral reduction mammoplasty by the same surgeon. The intervention group received 1 g of intravenous TXA at anesthesia induction and local infiltration with a 1-mg/mL TXA vasoconstrictive solution containing epinephrine. The control group received local infiltration with an identical vasoconstrictive solution that did not contain TXA. Primary outcomes were total and daily drain output. Secondary outcomes included length of hospital stay, time to drain removal, and postoperative complications. Results Fifty-seven patients were included (31 in the control group and 26 in the intervention group). TXA significantly reduced the total postoperative drain volume ( p <0.001) by an estimated 79% and drain output at 24h ( p <0.003). In the TXA group, 53.8 % of the patients had unquantifiable drainage versus 9.7% in the control group ( p =0.002). No significant differences were observed in complications, including hemorrhagic events, infections, or wound healing; indeed, the incidence of complications was low in both groups. Conclusions Combined TXA therapy significantly and clinically meaningfully reduced postoperative drain output. This reduction anticipates drain removal and may ultimately contribute to the broader adoption of drain-free breast reduction surgery. Level of Evidence II This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine Ratings, please refer to Table of Contents or online Instructions to Authors www.springer.com/00266 .